Efektifitas Media Pembelajaran Berbasis Tradisi Budaya Pesisir dalam Proyek P5 terhadap Minat Belajar Siswa di MTSn 3 Tuban - Karara Dwi Krisnaeni; Fatimatuz Zahro (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the influence of coastal cultural tradition-based learning media in the implementation of the Pancasila Student Profile Strengthening Project (P5) on students' learning interest at MTsN 3 Tuban. The background of this research is the lack of integration of coastal local wisdom in learning while the characteristics of madrasah students require a contextual approach that connects material with the surrounding environment. The study uses a quantitative approach with a pretest -experimental design involving 36 eighth-grade students as samples. The research instrument is a learning interest questionnaire with a Likert scale covering aspects of attention, interest, involvement, and continuous desire. Data were analyzed using descriptive statistics and normalized gain test. The results showed a significant increase in students' learning interest with an average score increasing from 68.75 in the pre-test to 82.94 in the post-test with an N-Gain value of 0.45 in the medium category. These findings identify that coastal cultural tradition-based learning media have a positive impact on increasing students' learning interest through contextual and meaningful learning.